TEACHER PERFORMANCE ECONOMIC DIFFERENCE IN LEVEL BETWEEN STATE junior CERTIFICATION WITH THAT WHICH HAS NOT BEEN AND CERTIFICATION IN DISTRICT shadows KOTO IN THE DISTRICT XI Tarusan - febrina, Yesi - (Pendidikan Ekonomi, 2014)
The subject is examined in this study is how the relationship pedagogical ability, personality,social and professional towards economics teacher performance differences that have been certifiedand are not yet certified. This research was conducted at the level of Junior High School in DistrictDistrict of Bayang and Koto XI Tarusan economy where the population is teachers who are alreadycertified and who have not been certified, and the sampling technique using total sampling. Data werecollected through a questionnaire or a questionnaire. Data were analyzed by chi-square analysismethods.The results showed that: In hypothesis testing chi square analysis results showed chi-squarevalue of 415.508 with a p-value 0.073 value. Since the value of p-value 0.073> 0.05 means that thereis no difference between teacher certification with the performance of non-certified teachers. Rank ofthe output can be seen that the mean value for non-certified teachers (0) is smaller than the value ofteacher certification (33.25 <41.88). From Mann_Whitney U test analysis can be seen in the output of